Functional characterization of the interactions between CTCF truncated transcriptional factor with y-box binding protein-1 and the CTD of POL II - Azman, Daruliza Kernain Mohd (2016)
CCCTC sequence binding factor (CTCF) involved in the regulation of transcription, insulator function, control of imprinting and the X-chromosome inactivation. Two of the CTCF protein interacting partners were the transcriptional factor YB-1, a member of the Y-box binding protein 1 and the second protein was the large subunit of RNA polymerase II (LS Pol II) the principal enzyme for transcription. Previous studies have shown the interaction between CTCF and YB-1 occurred at the Zinc finger (ZF) and Cold Shock Domain (CSD) respectively whereas the interaction between CTCF and RNA Pol II occurred at the C-terminal domains (CTD) for both proteins. The objectives of this study are to determine the interaction between CTCF and YB-1 in Recurrent Glioblastoma Multiforme (RGBM) cell line and to identify the motif within CTCF CTD that is critical for binding with RNA Pol II CTD. CTCF truncated proteins were produced and used to map the interaction to YB-1 in RGBM cell line. The interaction of these truncated proteins was mapped using co-immunoprecipitation (Co-IP) and pulldown assay and the functional significant of the interaction was characterized via mammalian two hybrid system. On the other hand, CTCF and RNA Poll II interactionswere characterized by identifying two sites within CTCF C-terminal domain important for the interaction and seven candidates CTCF C mutant variants named 1A, 1B, 1A1B, 2A, 2B, 2A2B and CM deficient for binding with Poll II CTD were produced. The interaction of these mutants to Poll II CTD was characterized via Coimmunoprecipitation (Co-IP) and pull-down assay, while the ability of these mutants to induce apoptosis in recurrent glioblastoma multiforme (RGBM) cell line was also analysed using Caspase 3/7 Glo assay. From the results obtained for CTCF and YB-1 interactions, the co-immunoprecipitation (co-IP) showed that CTCF was able to form a complex with YB-1 in the RGBM total cell lysate. From pull down assay results, CTCFZF was the only domain binds with YB-1 Cold Shock Domain (CSD) and the rest of domains fail to interact. As for CTCF and RNA Pol II interactions, the Co-IP results shown positive interaction for CTCF wild-type and all the mutant variants in RGBM cell line. The interaction was further characterized using pull-down assay and EEEE motif was identified as a critical motif for binding to Pol II CTD. The effects of CTCF C mutant variants on cell death by apoptosis assay showed that CTCF complete mutant (CM) induced highest apoptosis percentage in the cell as compared to the wild-type CTCF. As conclusion, CTCF ZF domain was found to interact with YB-1 CSD in RGBM cell line and the important motif in CTCF C terminal region critical for Poll II CTD binding was successfully identified. The EEEE motif was found to be a critical motif for binding; hence further study is needed to determine the significant of these motifs in CTCF and RNA Poll II interactions.